Pengaruh Kompetensi Manajerial Kepala Sekolah dan Kinerja Guru Terhadap Mutu Layanan Pendidikan di MTs Negeri 4 Jombang - Rosyidi, Muhammad; Suwandi, Suwandi (Jurnal Manajemen Pendidikan Islam (MANAPI), 2025)
This study aims to analyze the extent to which the principal's managerial competence and teacher performance influence the quality of service at MTs Negeri 4 Jombang. Using a quantitative approach with an ex post facto method in the form of causal associative, data were collected through a closed questionnaire to 117 teacher respondents. Using a saturated sampling method. The instrument consists of 33 questions. The results of the F test show a calculated F value of 72.151> 2.68, which means that both independent variables simultaneously have a significant influence on the quality of service. This emphasizes the importance of cooperation between principal leadership and teacher performance in improving the quality of education services. Therefore, improving the quality of service requires collaboration between the principal and teachers. Both must continue to improve their respective capacities so that the quality of education services can continue to be improved sustainably, the quality of education in madrasas.